2019
DOI: 10.3390/nu11081938
|View full text |Cite
|
Sign up to set email alerts
|

A 5Ad Dietary Protocol for Functional Bowel Disorders

Abstract: Functional bowel disorders (FBDs) affect around 20% of the population worldwide and are associated with reduced quality of life and high healthcare costs. Dietary therapies are frequently implemented to assist with symptom relief in these individuals, however, there are concerns regarding their complexity, restrictiveness, nutritional adequacy, and effectiveness. Thus, to overcome these limitations, a novel approach, the 5Ad Dietary Protocol, was designed and tested for its efficacy in reducing the severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…However, as FODMAPs are all within the carbohydrate category, there are still people who would not benefit from a LFD approach if, for example, their symptoms arise in response to gluten, dietary lectins, or food additives/chemicals. Additionally, the requirement of supervision from a dietitian for those following the LFD implies inherent safety concerns with the LFD and also confirms our own and the authors' published view about the LFD [18], that is, Shaw et al (2019) [1]. A recent meta-analysis concluded that very low-quality evidence exists that the LFD is effective in reducing symptoms in IBS patients [23].…”
Section: Is the Lfd Alone The Ultimate Choice For People With Fbds?supporting
confidence: 80%
See 2 more Smart Citations
“…However, as FODMAPs are all within the carbohydrate category, there are still people who would not benefit from a LFD approach if, for example, their symptoms arise in response to gluten, dietary lectins, or food additives/chemicals. Additionally, the requirement of supervision from a dietitian for those following the LFD implies inherent safety concerns with the LFD and also confirms our own and the authors' published view about the LFD [18], that is, Shaw et al (2019) [1]. A recent meta-analysis concluded that very low-quality evidence exists that the LFD is effective in reducing symptoms in IBS patients [23].…”
Section: Is the Lfd Alone The Ultimate Choice For People With Fbds?supporting
confidence: 80%
“…These factors, combined, are likely responsible for the significant improvements observed within a week in the studied group [18]. Thus, the 5AdD is deemed a natural development, built on the common dietary therapies, and aims to streamline the delivery and adherence without compromising safety and nutritional adequacy [18].…”
Section: The Similarities Between the 5add And Current Dietary Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We read the article by Ibrahim and Stribling [1] with interest, as dietary therapies for functional disorders can be challenging to implement, such as the initial phase of the low fermentable oligo-, di-, mono-saccharide and polyols (FODMAPs) diet. In view of this, streamlined approaches to achieve symptom management maybe warranted, such as a 'bottom up' approach.…”
mentioning
confidence: 99%
“…117 The 5Ad Dietary Protocol, is said to be a less restrictive dietary approach than low FODMAP and helped abdominal pain in a small pilot study (22 subjects, mixed functional bowel disorders). 118 A 4-week starch-and sucrose-reduced diet reduced abdominal pain in patients with IBS (80 patients) compared to controls (25 patients) with a 74%, responder rate. 119 Sustained (small intestine) release peppermint oil is classed as a medical food and in a small, 4-week RCT for patients (35 patients) with non-constipated IBS was better than placebo (37 patients) in reducing abdominal pain severity.…”
Section: Novel and Emerg Ing Ibs Pain Manag Ement Approache Smentioning
confidence: 99%